Aprendizagem ao longo da vida uma proposta de ensino em autocuidado com idosos da Universidade da Maturidade da Universidade Federal do Tocantins - Barcelos, Alexandre dos Santos (2021)
Aging is considered the greatest achievement of the 21st century. Self-care is considered one of the determinants of active aging proposed by WHO. Self-care is how individual deals with his health in all aspects, such as actions to promote, prevent and take care of himself. However, for this approach to be effective, strategies must be collaborative, aiming at greater awareness and encouraging healthy, realistic and economically accessible choices for the population, that is, dialogued and integrated with the reality of the public served. Therefore, it is necessary to include this theme in lifelong learning programs. Thus, the aim of this study was to assess the impact of a teaching proposal on engaging self-care in elderly members of a lifelong learning project based on a quasi-experimental study with a quantitative approach. To characterize the sample, two questionnaires were applied, a socioeconomic questionnaire and the Appraisal of Self-Care Agency Scale (ASA-A) questionnaire. Both were applied before and after 06 meetings with 14 elderlies at the University of Maturity at the Federal University of Tocantins. To evaluate the workshops, the elderly answered a semi-structured questionnaire after each workshop. The average score before the pedagogical proposal was 94.57 ± 21.81 and after 103.78 ± 2.22. There was a tendency to improve the score after the application of the pedagogical proposal (P = 0.082). Although there was no statistically significant difference, a lesser dispersion in the responses can be observed, at the moment after the application of the pedagogical proposal. Female gender (P = 0.040) and higher education (P = 0.047) were associated with the improvement in the scores of the ASA-A questionnaire. Regarding the evaluation of the workshops by the elderly, the duration of the expository classes discussed was considered adequate in 72.4% of the answers, 44.8% understood in part the content of these classes and 48.3% of the answers classified the content of these classes as very important and 48.3% manage to pass on the content learned in this class. We emphasize that the group discussion methodology presented the highest frequency of responses on adequate duration (85.7%), the highest frequency of understood everything (42.9%) in the category on understanding and the highest frequency of very important responses (64.3%), but the methodologies used in the workshops were not associated with the level of understanding of the individuals. In the baseline, the elderly showed a high engagement in self-care, a condition that was increased by 64.3% of the elderly with the workshops. Sex and education are associated factors in the profile of elderly people who improved performance for self-care. In the workshops, the group discussion methodology in the dynamics was the best evaluated by the elderly. We suggest using this methodology in educational activities and further analysis as to using other types of methodology at UMA/UFT in the self-care discipline. We recommend carrying out studies including other analyzes, such as personal factors, socioeconomic factors, environmental factors, interpersonal influences, situational influences, studies with other designs and, further analysis on the level of understanding of the elderly.